2017
DOI: 10.1111/ppl.12529
|View full text |Cite
|
Sign up to set email alerts
|

Special trends in CBF and DREB2 groups in Eucalyptus gunnii vs Eucalyptus grandis suggest that CBF are master players in the trade‐off between growth and stress resistance

Abstract: Annotation of the Eucalyptus grandis genome showed a large amplification of the dehydration-responsive element binding 1/C-repeat binding factor (DREB1/CBF) group without recent DREB2 gene duplication compared with other plant species. The present annotation of the CBF and DREB2 genes from a draft of the Eucalyptus gunnii genome sequence reveals at least one additional CBF copy in the E. gunnii genome compared with E. grandis, suggesting that this group is still evolving, unlike the DREB2 group. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…Eucalyptus can increase freezing tolerance by cold acclimation as well as other plant species. CBF genes have been cloned from Eucalyptus [20,21,22,25] and their overexpression in cold-sensitive Eucalyptus could improve the freezing tolerance [23]. Cao et al further reported that there were 17 CBF orthologs in the E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eucalyptus can increase freezing tolerance by cold acclimation as well as other plant species. CBF genes have been cloned from Eucalyptus [20,21,22,25] and their overexpression in cold-sensitive Eucalyptus could improve the freezing tolerance [23]. Cao et al further reported that there were 17 CBF orthologs in the E .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to discover the molecular regulation mechanism of cold response and carry out genetic improvement on freezing tolerance in Eucalyptus . Although CBF genes have been isolated and characterized from Eucalyptus [20,21,22,23,24,25], the knowledge about its upstream regulator ICE1 and its positive and negative regulation pathway needs to be investigated. Our precious studies have revealed that ectopic expression of EcaICE1 from E. camaldulensis confers improved cold tolerance and the expression level of downstream genes in transgenic tobaccos [16].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, CBF genes are overrepresented in the E. grandis genome as compared to most other plant genomes with the exception of Medicago that also contains 17 CBF members [22]. This subfamily expansion is even more important in E. gunnii, which is one of the most frost-tolerant Eucalyptus [23]. Some of these CBFs are strongly induced in stems in response to cold treatment [23].…”
Section: Introductionmentioning
confidence: 99%
“…This subfamily expansion is even more important in E. gunnii, which is one of the most frost-tolerant Eucalyptus [23]. Some of these CBFs are strongly induced in stems in response to cold treatment [23]. To the best of our knowledge, no study has ever investigated the effects of CBF overexpression on secondary growth and wood formation.…”
Section: Introductionmentioning
confidence: 99%
“…The CBF/DREB1 belonging to the A-1 subgroup are mainly participated in plant response to low temperature (Akhtar et al, 2012). CBF genes have been found in a wide range of plants, such as AtCBFs from Arabidopsis thaliana (Gilmour et al, 2004), BnCBFs from Brassica napus (Jaglo et al, 2001), CbCBF from Capsella bursa-pastoris (Wang et al, 2004), CfCBF3 from sweet pepper (Yang et al, 2011), EglCBFs from Eucalyptus (Nguyen et al, 2017;Navarrete-Campos et al, 2017), HvCBF3 from barley (Choi et al, 2002), LpCBF3 from perennial ryegrass (Xiong & Frei, 2006), OsCBF1 from rice (Choi et al, 2002), PpCBF3 from bluegrass (Zhuang et al, 2015), PaCBF from sweet cherry (Kitashiba et al, 2004), ScCBF from rye (Jaglo et al, 2001), LeCBFs from tomato (Zhang et al, 2004), TaCBFs from wheat (Babben et al, 2018), TmCBFs from Triticum monococcum (Miller et al, 2006), VvCBFs from grapevine (Londo & Garris, 2015), and ZmCBF3 from maize (Wang et al, 2008). CBF proteins contain several conserved domains including the DNA-binding domain -AP2, the N-terminus nuclear localization signal (NLS), and the acidic domains present in C-terminus.…”
Section: Introductionmentioning
confidence: 99%